2016
DOI: 10.3109/19401736.2015.1136304
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial haplogroup D4j specific variant m.11696G > a( MT-ND4 ) may increase the penetrance and expressivity of the LHON-associated m.11778G > a mutation in Chinese pedigrees

Abstract: Genetic variants of mitochondrial DNA (mtDNA) were implicated to be associated with male infertility. Our previous whole mitochondrial genome sequencing and association study has identified two susceptibility mtDNA variants for oligoasthenospermia in Han Chinese men. In this study, we tested promising associations in an extended validation using 670 idiopathic oligoasthenospermia cases and 793 healthy controls to identify additional risk variants. We found that the genetic variant of m.11696G>A showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In these two families, the age of onset for visual impairment ranged between 6 and 32 years old (average, 20.5 years old). Previous studies confirmed that the age of onset for visual impairment in the two pedigrees harboring the m.5587T>C mutation was similar to that in other Chinese families with LHON carrying the m.11778G>A mutation (28)(29)(30)(31)(32). In contrast, a number of Chinese subjects carrying the m.11778G>A mutation, which exhibited profound visual loss, the affected subjects carrying the m.5587T>C mutation suffered from mild to profound visual impairment, similar to that exhibited in patients carrying m.3394T>C, m.3635G>A, m.3866T>C, m.11696G>A, m.12238T>C and m.14502T>C mutations (15)(16)(17)(18)(19)33).…”
Section: Discussionsupporting
confidence: 71%
“…In these two families, the age of onset for visual impairment ranged between 6 and 32 years old (average, 20.5 years old). Previous studies confirmed that the age of onset for visual impairment in the two pedigrees harboring the m.5587T>C mutation was similar to that in other Chinese families with LHON carrying the m.11778G>A mutation (28)(29)(30)(31)(32). In contrast, a number of Chinese subjects carrying the m.11778G>A mutation, which exhibited profound visual loss, the affected subjects carrying the m.5587T>C mutation suffered from mild to profound visual impairment, similar to that exhibited in patients carrying m.3394T>C, m.3635G>A, m.3866T>C, m.11696G>A, m.12238T>C and m.14502T>C mutations (15)(16)(17)(18)(19)33).…”
Section: Discussionsupporting
confidence: 71%
“…We further used an online application (http://www .mitotool.org/genomeRSRS.html) in order to determine the mitochondrial haplogroup of the proband and related individuals, consistent with current haplogroup nomenclature [17,18].…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…We further used an online application (www.mitotool.org/genomeRSRS.html) in order to determine the mitochondrial haplogroup of the proband and related individuals, consistent with current haplogroup nomenclature [17,18].…”
Section: Phylogenetic Analysesmentioning
confidence: 99%